(untitled) (Research, Society and Development, 2023)
Objective: to identify, in the state of the art, the relationship between oral health, health promotion and the elderly. Methods: narrative review. Methods: narrative review carried out from May 1 to December 11, 2022 in the following national and international databases: National Center for Biotechnology Information National Institutes of health (PUBMED), Scientific Electronic Library Online (SciELO), SciVerse Scopus (Scopus) and descriptors: “oral health”, “health promotion” and “elderly”. 608 articles were found, of which 67 constituted the final sample. The material was analyzed and organized using the Rayyan application. Results: from the association of the results found in the word cloud analysis and the main results of the 67 articles presented, it can be highlighted that most studies on oral health promotion have focused on interventions to improve the quality of life of the elderly, in addition to pathologies associated with lack of oral health care. Conclusion: it is expected that the findings of this study can favor health professionals, in order to understand the importance of promoting oral health in the elderly, favoring the direction of care.